STIGMA AROUND MENTAL HEALTH: BARRIERS TO SEEKING HELP (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Mental health stigma remains one of the most significant obstacles to global public health. This paper explores the psychological, social, and systemic barriers that prevent individuals from seeking professional help. By analyzing the different layers of stigma—from self-perception to societal labels—this article highlights how fear of judgment and lack of awareness contribute to untreated mental health conditions.